Complex molecular surfaces and interfaces: Sheffield, UK 24-26 July 2017 - Amabilino, David B. (Faraday discussions, 2017)
This volume focuses on understanding the interaction of molecules with surfaces and their subsequent organisation, reactivity, or properties from both experimental and theoretical perspectives. The unique behaviour of compounds confined at interfaces can be very different from those in bulk environments. Advances in methods and their understanding for the determination of the structure and chemical bonding at surfaces is central to continued progress in the field. Among the questions that need answering are: how is chemical reactivity modified at surfaces and how can we optimise it for selective and efficient processes? How reliable are the actual methods for determining molecular conformation at surfaces? How can we control diffusion of molecules at surfaces in order to influence growth? Can two-dimensional structure be correlated with three dimensional order? How can we make use of single molecule properties at an interface? Interfacial processes are also at the heart of the function of many materials, the properties they exhibit and chemical reactions they can perform